2011
DOI: 10.1143/jjap.50.071101
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of Electrical Conductivity by Oxygen Vacancies and Charge Carrier Trapping at Interface between CoO and Electrodes

Abstract: Recently, the role of resistance random access memory (RRAM) is becoming extremely important in the development of nonvolatile memories. RRAM works by changing the resistance of the transition metal oxide contained in RRAM after the application of a sufficiently high voltage, however, this switching mechanism has not been fully clarified. In this study, by performing first principles calculations based on the density functional theory, we first investigate the change in the property of bulk CoO resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Since ReRAMs were first reported, clarification of their operating principles has been a hot topic. [31][32][33][34][35][36][37][38][39] The operating principles are roughly divided into two models: (1) a filament model, in which conductive paths connecting electrodes are locally formed on the device plane, and (2) an interface model, in which the resistance of devices with a MOM structure changes owing to a change in the Schottky barrier height and other factors at the entire metal/oxide interface. A typical example of (1) includes the Ni nanofilament deposited on NiO grain boundaries reported in 2009.…”
Section: Operating Principle Of Memorymentioning
confidence: 99%
“…Since ReRAMs were first reported, clarification of their operating principles has been a hot topic. [31][32][33][34][35][36][37][38][39] The operating principles are roughly divided into two models: (1) a filament model, in which conductive paths connecting electrodes are locally formed on the device plane, and (2) an interface model, in which the resistance of devices with a MOM structure changes owing to a change in the Schottky barrier height and other factors at the entire metal/oxide interface. A typical example of (1) includes the Ni nanofilament deposited on NiO grain boundaries reported in 2009.…”
Section: Operating Principle Of Memorymentioning
confidence: 99%
“…[6][7][8][9] Most of the papers explain these switching behaviors using a metallic filament model or oxygen migration mechanism. [10][11][12][13][14][15][16] We also reported that negative differential resistance (NDR) behaviors in the current-voltage (I-V) curve are responsible for the EIR properties of PCMO. 17) We speculated that the oxidation/reduction process between the electrode and base material could play an important part in the EIR phenomenon.…”
Section: Introductionmentioning
confidence: 96%
“…Being a strong contender for resistive switching memories, transition metal oxides (TMO), 8) especially binary oxides, have been investigated recently. Among other various oxides such as HfO x , [9][10][11][12] WO x , [13][14][15] ZrO 2 , [16][17][18] CoO, 19,20) TiO 2 , [21][22][23][24] CuO, 25,26) Ta 2 O 5 , [27][28][29][30][31] NiO, 32) Nb 2 O 5 , 33) and AlO x , [34][35][36] tantalum oxide (TaO x )-based devices are becoming attractive owing to their ease of deposition using existing conventional systems, high thermal stability, compatibility with CMOS processes and high dielectric constant (" r $ 25). Commonly, the use of platinum (Pt) as an electrode material in a Pt/Ta 2 O 5 /Pt structure 28) is reported for RRAM applications owing to its high work function and inertness.…”
Section: Introductionmentioning
confidence: 99%